Rapid and Efficient Construction of Indolizino[3, 4, 5‐ab]isoindole Skeletons by a Rhodium‐Catalyzed Tandem Reaction. Issue 1 (5th December 2019) - Liu, Chang; Wu, Shaonan; Sun, Wan; Meng, Haifang; Xing, Siyang; Zhu, Bolin
Abstract: A facile rhodium‐catalyzed tandem reaction of two molecules of acrylates with two molecules of 2‐phenylpyridines involving sequential C−H activation, Michael addition, [12+2] cycloaddition and oxidative aromatization has been described. A series of indolizino[3, 4, 5‐ ab ]isoindole compounds were efficiently afforded in good yields by the formation of two C−C bonds, two C=C bonds and one C−N bond. Abstract : All‐in‐one ! A facile rhodium‐catalyzed tandem reaction involving sequential C−H activation, Michael addition, [12+2] cycloaddition and oxidative aromatization has been developed for the synthesis of indolizino[3, 4, 5‐ ab ]isoindoles by the formation of two C−C bonds, two C=C bonds and one C−N bond.